Implementation of Sibi And Bisindo Letters Recognition Using Augmented Reality During Pandemic - Putu Wirayudi Aditama; I Gede Adi Sudi Anggara; I Nyoman Jayanegara (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
BISINDO or Indonesian Sign Language is one of the sign systems used in Indonesia. BISINDO comes from the first language or mother tongue for the deaf. The phenomenon of the Covid 19 pandemic has changed the world of education globally. The results of a survey of people with hearing impairments in Bali, especially in Denpasar, showed that 72 respondents, 62.5%, stated that it was difficult to understand the learning process carried out at home during the pandemic. 37.5% indicated that they had no difficulty understanding the learning process at home during the pandemic. According to respondents, 75.7% of respondents chose BISINDO, which is easy to understand and 24.3% chose SIBI. An augmented reality application was designed to recognize the BISINDO alphabet from this data. This application is expected to provide a solution to make it easier for deaf people to understand BISINDO sign language during a pandemic. SIBI is an adaptation of American Sign Language which is currently applied in special schools (SLB). To provide support in learning SIBI sign language, in advance of technology, the design of Augmented Reality to introduce SIBI letters will help in the learning process. The results of the black box test show that all the features and functions of the application can run well. In observing the response time when scanning markers using the Xiaomi PocoF1 marker on the SIBI letters, the average time is 6.05 seconds. Observation of the scan distance of SIBI letters, the average scan distance of markers that can be scanned at a distance of 5 cm to 50 cm.